The Effectiveness of Transformational Leadership: : A Qualitative-Based study on Millennial perceptions in South Africa - Davids, Inga; Appiah, Kenneth; Davids, Gregory; Ofori, Felix Nana Kofi (Archives of Business Research, 2021)
The purpose of this study/article is to exmaine whether the individualistic nature of millennials undermines the the effrots of transformational leadsrhip in achieving organizational objectives.